2014
DOI: 10.1177/1932296813516955
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Lens Autofluorescence Can Distinguish Subjects With Diabetes From Those Without

Abstract: Lens autofluorescence is increased in patients with diabetes mellitus, but clinical application has been limited by the lack of an instrument suitable for routine clinical use. We investigate possible uses of a new scanning confocal biomicroscope (1) to identify subjects with undiagnosed type 2 diabetes and (2) as a marker for the progression of diabetes. One hundred seventyeight subjects self-reported as normal and 53 subjects physician-diagnosed with diabetes or prediabetes were recruited. Measurements were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
2
21
1
Order By: Relevance
“…29 In this study, we also found significant relationships between the LFR and both HbA 1c levels and the duration of diabetes, which is consistent with the literature. 33,34 On the other hand, we did not find any relation with age and lens fluorescence. One of the reasons may be that in most studies showing that increased fluorescence intensity is associated with increasing age the study population comprised of healthy volunteers.…”
Section: Assessment Of Diabetic Peripheral Neuropathycontrasting
confidence: 85%
See 1 more Smart Citation
“…29 In this study, we also found significant relationships between the LFR and both HbA 1c levels and the duration of diabetes, which is consistent with the literature. 33,34 On the other hand, we did not find any relation with age and lens fluorescence. One of the reasons may be that in most studies showing that increased fluorescence intensity is associated with increasing age the study population comprised of healthy volunteers.…”
Section: Assessment Of Diabetic Peripheral Neuropathycontrasting
confidence: 85%
“…13,17 Another possibility is that the effect of age on fluorescence intensity may not be observed in the presence of high blood sugar, because high blood sugar prominently affects the fluorescence intensity of the lens. 14,33,34 In conclusion, high LFR was found to be related with either small or large nerve fiber damage, or both. Although with the high specifity of the results, age-adjusted LFR measurements with the ClearPath DS-120 biomicroscope yield significant outcomes in the diagnosis of neuropathy, the instrument seems to have low sensitivity.…”
Section: Assessment Of Diabetic Peripheral Neuropathymentioning
confidence: 79%
“…However, recently, a new confocal biomicroscope is available to measure lens AF in a fast, noninvasive, and reproducible manner. 8 , 14 The range of FRs which are used in this instrument was reported to change between 0.07 and 0.33 in 127 healthy subjects aged between 21 and 70. 7 Lens AF was found to increase with age.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the buildup of AGEs in long-lived proteins (Hammes et al, 1999; Sell et al, 1992; Vashishth, 2009). One human study that quantified autofluorescence of eye lens as an indicator of AGE accumulation with age (Cahn et al, 2014). The buildup of different AGEs (e.g., pentosidine) in the skin and increased crosslinking of collagen due to AGEs has been observed in the skin biopsies of diabetic patients (Monnier et al, 2005; Sell et al, 1992).…”
Section: The Maillard Reaction: Initiators Propagators and Chemistrymentioning
confidence: 99%